(ليبيا نموذجا)آثار الهجرة الإفريقية غير الشرعية إلى أوروبا على بلدان العبور - Mohammed Ebeid Azzentani Ibrahim
No doubt that the phenomenon of illegal migration represents a potential risk that threatening the security of any country in the world, whether importer or exporter of illegal migrants or a transit country, moreover this phenomenon affect international relationships, and therefore this research aims to the evaluate the impact of illegal African migration to Europe through the territory of Libya as a transit country. In addition to that the study aims to identify the efforts of domestic authorities that have spent great efforts to control illegal migration and to remedy the negative impacts of this phenomenon and its motives. Migration occurs due to many reasons such as economic, politics, security, social and psychological problems as well as natural disasters and the spread of diseases, also this phenomenon happens due to the proximity and similarity of cultures, languages, customs and traditions, and at the same time produce negative impacts on transit countries such as "Libya", and these impacts are economical, political, social, cultural, on health, security and the spread of crime and fiaud and sorcery, currency counterfeiting, money smuggling, illegal sexual practices, the spread of drugs between Libyan young people, drinking alcohol, increasing the incidents of cars stealing, and the spread of begging in many Libyan cites. Moreover the increase of divorce rate and initiating differences between Libyan citizens, and lead to the increase the rate of polygamy cases, also the formation of human trafficking gangs, and trading in human organs, cut off the power supply, the spread of infectious diseases, create a black market and corrupt sale of goods and rising prices of goods in the market. Furthermore the spread of corruption among security men and government staff in Libyans, and imitating the habits of illegal migrants by Libyan young people, and comparing the advantages of illegal migration are few such as the availability of cheap labour force and increasing the number of labour force in the market, but this situation conversely lead to unemployment and affect the security of Libya. The study emphasized that the role of domestic authorities was insufficient to control this phenomenon; also some of their decisions were not effective. This study recommend to impose certain conditions to enter Libyan borders and to encourage mutual cooperation between Afi-ican countries to control and reduce illegal migration, and to encourage the political settlement of disputes and the elimination of military coups in many Afiican continent and directing attention to the development of Afiican countries.